Potensi Pemanfaatan Sumber Energi Alternatif Gas Metana untuk Pembangkit Listrik 3 MW Menggunakan Pemodelan Landgem (Studi Kasus: TPA Koya Koso Kota Jayapura) - Royend F. Samosir; Johni Jonatan Numberi; Enos Karapa; Herbert Innah; Yane Ansanay; Prihananto Setiadji; Tiper K. M. Uniplaita (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2023)
The volume of waste will continue to increase with increasing time, population, and economic growth in a city, district, or province. The city of Jayapura, as the center of the economy of the land of Papua, is the same way. The Koya Koso TPA management system for Jayapura City is currently landfill control, where the waste that has been collected at the TPA is stockpiled using layers of soil so that the piles are increasing in number day by day and causing problems including air pollution by methane gas, CO2, and other gases and limited land, thereby reducing the age of TPA Koya Koso Jayapura City. This study aims to determine the potential content of methane gas by modeling it using Landgem software and the potential capacity of electrical energy that can be generated. The results showed that the potential content of methane gas generated from Landgem modeling is 13,134,026 m3/year, or 8,762 tons/year, resulting in a potential capacity of electrical energy of 2,797.22 kW, or 2.8 MW.